Determinants of a Variety of Deviant Behaviors: An Analysis of Family Satisfaction, Personality Traits, and Their Relationship to Deviant Behaviors Among Filipino Adolescents - Dullas, Angelo Reyes; Yncierto, Kristine Danielle; Labiano, Mariel A.; Marcelo, Jerome C. (Frontiers in Psychology, 2021)
This study was designed to look for the possible predictors of deviant behavior, as well as its association among family satisfaction and personality traits. Deviant behavior is the behavior that does not follow an established rule or laws that provided by the society (Hanmoglu, 2018). A total of 1500 Filipino adolescents were selected. Scales such as DBVS (Sanches et. al., 2016), SWFL (Zabriskie and McCormick, 2003) and BFI (John et al., 2008) were utilized. Regression analysis, Pearson-correlation, and T-test was used to analyze this study. The current study found that there are differences in levels of deviant behavior (Minor and Severe infractions) among sexes. Additionally, current study found that there is association between family satisfaction and deviant behavior. Further, respondents who participate more in deviant behavior are found to be less satisfied in their family life, while respondents who participate less in deviant behavior are more satisfied in their family life. Lastly, current study found that personality traits of agreeableness are found to be the best predictors of deviant behavior among adolescents. The findings suggest critical implication on the role of personality traits and family satisfaction on deviant behaviors.